Improvement of a Free-Wake Model for the Aerodynamic and Aeroacoustic Analysis of a Small-Scale Two-Bladed Propeller in Hover - Manuel Iannotta; Antonio Visingardi; Domenico Quagliarella; Fabrizio De Gregorio; Mattia Barbarino; Alex Zanotti (Aerospace)
The aim of the present work is the improvement of a free-wake model for the analysis of a small-scale two-bladed propeller in hover. The simulations are carried out using a BEM approach implemented in the medium-fidelity solver RAMSYS. An acoustic validation is also performed using the developed tool ACO-FWH. The work proves that even mild discrepancies in the propeller geometry must be accounted for as their influence is not negligible, especially on the aeroacoustics of the propeller. In particular, the proper modeling of the blades enables the correct identification of the sub-harmonics of the SPL spectra. An optimization procedure based on the application of the evolutionary Genetic Algorithm is followed to identify the values of the parameters describing the dissipative and diffusive properties in the Bhagwat–Leishman vortex core model, an upgraded version of the classical Lamb–Oseen one. On average, this approach enabled the further improvement of the accuracy of the numerical model in terms of acoustic signature evaluation with respect to the one obtained by only modeling blade dissimilarities. The results obtained demonstrate the promising capabilities of a fine-tuned free-wake medium-fidelity approach to simulate the aerodynamic and acoustic details of a small-scale propeller in hover, provided the accurate geometrical modeling of the propeller and the selection of suitable parameters to be used in the wake modeling.